Kontribusi Permainan Tradisional Terhadap Karakter Keterbukaan Pikiran Anak Usia 10-12 Tahun - Widyati, Dwi Rahayuning; Nugrahanta, Gregorius Ari (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this researched was to develop a character education guidebook for open-mindedness based on traditional games for children aged 10-12 years. The problem statement of the researched was how to develop a traditional game-based character education guidebook, how was the quality of the guidebook, and did the guidebook affected the open-mindedness character of children. The researched model used was R & D typed ADDIE. The results of the studied explained that 1) the open-mindedness character education guidebook based on traditional games was developed used the ADDIE stages; 2) the quality of the character education guidebook got a score of 3.87 (range 1-4) which was classified in the category of